Impaired long-term potentiation and long-term memory deficits in xCT-deficient sut mice. Issue 3 (26th March 2012) - Li, Yan; Tan, Zhibing; Li, Zhigang; Sun, Zhongsheng; Duan, Shumin; Li, Wei
Abstract : xCT is the functional subunit of the cystine/glutamate antiporter system xc −, which exchanges intracellular glutamate with extracellular cystine. xCT has been reported to play roles in the maintenance of intracellular redox and ambient extracellular glutamate, which may affect neuronal function. To assess a potential role of xCT in the mouse hippocampus, we performed fear conditioning and passive avoidance for long-term memories and examined hippocampal synaptic plasticity in wild-type mice and xCT-null mutants, sut mice. Long-term memory was impaired in sut mice. Normal basal synaptic transmission and short-term presynaptic plasticity at hippocampal Schaffer collateral–CA1 synapses were observed in sut mice. However, LTP (long-term potentiation) was significantly reduced in sut mice compared with their wild-type counterparts. Supplementation of extracellular glutamate did not reverse the reduction in LTP. Taken together, our results suggest that xCT plays a role in the modulation of hippocampal long-term plasticity.